National radon programmes and policies: the RADPAR recommendations - Bochicchio, F; Hulka, J; Ringer, W; Rovenská, K; Fojtikova, I; Venoso, G; Bradley, E J; Fenton, D; Gruson, M; Arvela, H; Holmgren, O; Quindos, L; et al. (Radiation protection dosimetry, 2014)
Results from epidemiological studies on lung cancer and radon exposure in dwellings and mines led to a significant revision of recommendations and regulations of international organisations, such as WHO, IAEA, Nordic Countries, European Commission. Within the European project RADPAR, scientists from 18 institutions of 14 European countries worked together for 3 y (2009-12). Among other reports, a comprehensive booklet of recommendations was produced with the aim that they should be useful both for countries with a well-developed radon programme and for countries with little experience on radon issues. In this paper, the main RADPAR recommendations on radon programmes and policies are described and discussed. These recommendations should be very useful in preparing a national action plan, required by the recent Council Directive 2013/59/Euratom.
Keywords: Humans; Radiation Monitoring; radiační ochrana; Radiation Protection; Environmental Exposure; znečištění vzduchu ve vnitřním prostředí; Radioactive Pollutants; Guidelines as Topic; vystavení vlivu životního prostředí; monitorování radiace; radioaktivní znečišťující látky; Radon; směrnice jako téma; lidé; Air Pollution, Indoor; radon